Religious Diversity and Public Pastoral Theology Is it Time for a Comparative Theological Paradigm? - Bidwell, Duane R. (2015)
Effective public pastoral theology in multi- and inter-religious contexts engages the richness of, is accountable to, and practices mutuality among myriad religious traditions, yet the risk of perpetuating Christian privilege is high. How, then, can pastoral theology address public issues for the benefit of all people without perpetuating Christian privilege or colonizing other religious traditions? My public theological response to a community conflict in Orange County's Little Saigon caused me to reconsider existing pastoral theological resources for public theology in the contexts of religious diversity and multiple religious bonds. I suggest a comparative theological paradigm-a "caring across traditions" that attends to and engages theological constructs in other religious traditions-as a complement to the communal-contextual and intercultural paradigms.
Keywords: GLBT inclusion; Little Saigon; Public Theology; communal-contextual; Comparative Theology; Inter-religious; Intercultural; Interfaith; Pastoral Care; Religious Diversity; Spiritual Care